The Answer is 42. On Data, Information and Knowledge - Bours, Dennis (2015)
A recent discussion with some colleagues on the differences between da ta, knowledge and information made me realize that there still is a lo t of confusion when it comes to the use of terms; confusion that goes well beyond my earlier blog post on indicators, measures and metrics.